Sibling spillover effects and educational outcomes in Ghana and Niger - Huafeng Zhang; Stein Terje Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
This study investigates the impact of sibling effects on children's educational outcomes in Ghana and Niger, with a focus on disability and gender disparities. Surveys conducted in both countries utilize the Washington Group Child Functional Module (WG-CFM) to identify children's disability status. The analysis reveals a performance gap for children with disabilities (CWD), highlighting the challenges they face compared to their peers without disabilities (CWOD). Gender disparities in school performance vary between countries, with girls outperforming boys in Niger but showing no significant differences in Ghana. While the study did not discover any significant sibling effects in impoverished Niger, these effects are significant for children with disabilities in Ghana. In Ghana, older sisters positively and significantly influence the performance of CWD, while younger siblings only negatively impact CWD girls. Overall, this study underscores the importance of addressing the gender bias that disfavours girls, especially among disadvantaged children such as CWD.
hdl:11250/3142135
Keywords: I24; 330; Educational outcomes; children with disabilities; sibling effects; gender; school performance; Niger; Ghana